Morphometric Analysis of the Host Effect on Phenotypical Variation of Belminus ferroae (Hemiptera: Triatominae) - Claudia Magaly Sandoval Ramirez; Elsa Evelia Nieves Blanco; Reinaldo Gutiérrez Marin; Diego Alexander Jaimes Mendez; Nelcy Ortiz Rodríguez; Fernando Otálora-Luna; Elis José Aldana (Psyche: A Journal of Entomology)
The Triatominae subfamily includes hematophagous insects, well known for their role as vectors for the Trypanosoma cruzi parasite, etiologic agent of Chagas’ disease. Belminus ferroae is a triatomine that showed an increased demographic fitness when cockroaches were used as hosts. Here we compare the centroid size (CS) and wing shape between B. ferroae parents and three successive generations (O1, O2, and O3) of their offspring fed on cockroaches or mice under laboratory conditions. Morphometric analysis of the wings bugs fed on cockroaches showed a significant reduction in CS in both sexes among all generations. Sexual size dimorphism (SSD) was observed in the insects fed on cockroaches (O2 and O3), as well as those bugs fed on mice (O2). Differences in the shape of wings were observed between parental and offspring wings when fed on mice, but not in males (O1, O2, and O3) or females (O1 and O2) fed on cockroaches. There was a greater wing shape similarity between the cockroach-fed offspring and their parents according to the Mahalanobis distances. Our results support the idea of higher adaptation of this Triatominae with arthropod hosts.